Diagnostic challenges in a case of an isolated third nerve palsy - Priya Sivakumar, M.S.; Savithri Palanive, DNB; Debasis Gochait, MD; Olivia Hess, BA (American Journal of Ophthalmology Case Reports, 2020)
Purpose: Neuro-ophthalmic manifestations may be the first and sole presenting feature of a nasopharyngeal carcinoma. Peri-neural spread is an emerging phenomenon that explains the distant spread of tumour cells well beyond the local extent of invasion. This under recognized route of tumour spread often results in delayed diagnosis and reduced life expectancy. The authors report a case of an isolated third nerve palsy as the only initial manifestation of nasopharyngeal carcinoma and emphasize the need for a high index of suspicion. Observation: The patient presented with left painful pupil involving complete third nerve palsy. Contrast enhanced imaging was initially deferred due to renal impairment. Plain MRI with MRA brain was normal. Hematology was suggestive of giant cell arteritis which is a rare but well documented cause of painful nerve palsies in the elderly. Unresponsiveness to steroids prompted contrast imaging with a reduced gadolinium dosing and hemodialysis backup which finally revealed a nasopharyngeal carcinoma. Conclusion and importance: This report is the journey of a third nerve palsy from a clinical diagnosis of an aneurysm (pupil involving palsy) to a probable diagnosis of giant cell arteritis (based on hematology) and to a final diagnosis of nasopharyngeal carcinoma (based on contrast imaging and immunohistochemistry)Nasopharyngeal carcinoma can be successfully cured if detected early. This report highlights the various manifestations of nasopharyngeal carcinoma and challenges faced in diagnosing this elusive tumor.